Dynamics of rural power structure: case study of an Indian village - Chaudhary, S. N. (Delhi, 1987)
The present work deals with the dynamics of rural power structure in an Indian village. It denotes that how most of the sources of power were in the hands of upper caste landlords during the British period. Because they had power sources in their hands they exercised number of excesses on lower castes. But after independence there has been trans fer of such sources of power from them to the middle caste. It also denotes that the new sources of power, which have emerged after independence, are dispersed among all the castes. The Book concludes that on the whole the socio-economic conditions of upper castes are deteriorating and there has been development in case of middle and scheduled castes and the latter two are no more monolith.
Keywords: Rural development-India